The Effect of Product Visual Aesthetics, Brand Identity Consistency and Sustainability Value on Product Purchasing Behavior in Islamic Business Perspective - Jeni Fitriyanti; Muhammad Iqbal Fasa; Is Susanto (International Publisher (YAPENBI), 2026)
This study aims to analyze the effect of product visual aesthetics, brand identity consistency and sustainability values on the purchasing behavior of N'PURE skincare products in Generation Z in Bandar Lampung. The research method used is quantitative with a descriptive and verification approach, where data were collected through questionnaires from 96 respondents and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS 4 software. The results showed that visual aesthetics and brand identity consistency had a positive and significant effect on purchasing behavior, while the value of sustainability did not show a partial significant effect. However, simultaneously, these three variables have a strong and significant impact in driving consumer purchasing decisions. The implication of this study confirms that manufacturers need to synergize attractive visual design with stable brand message integrity to win the market, while educating consumers on sustainability values so that environmental commitment can be transformed into real economic action in accordance with Islamic Business Principles.